Targeted therapy in patients with genetic tumor syndromes - Jahn, Arne; Heining, Christoph; Fröhling, Stefan; Glimm, Hanno; Schröck, Evelin (Medizinische Genetik, 2025)
Significant progress in comprehensive molecular diagnostics and targeted therapies for advanced malignancies has, in part, led to substantial improvements in patient outcomes. Nevertheless, comprehensive genomic profiling necessitates interdisciplinary discussion of potential clinical recommendations within interdisciplinary molecular tumor boards. (Likely) pathogenic germline variants (PGVs) typically warrant genetic counseling for patients and, where appropriate, their relatives. Concurrently, the rapidly expanding availability of targeted therapies introduces new therapeutic implications based on germline alterations that must be integrated into clinical decision-making. Moreover, the identification of PGVs may not only inform therapy in patients with manifest malignancy but also offer opportunities for targeted chemoprevention.
Gesehen am 02.03.2026